Biochemical and Cell Biological Properties of the Human Prohormone Convertase 1/3 Ser357Gly Mutation: A PC1/3 Hypermorph - Blanco, Elias H. (Endocrine Society, 2014)
Satiety and appetite signaling are accomplished by circulating peptide hormones. These peptide hormones require processing from larger precursors to become bioactive, often by the proprotein convertase 1/3 (PC1/3). Several subcellular maturation steps are necessary for PC1/3 to achieve its optimal enzymatic activity. Certain PC1/3 variants found in the general population slightly attenuate its enzymatic activity and are associated with obesity and diabetes. However, mutations that increase PC1/3 activity and/or affect its specificity could also have physiological consequences. We here present data showing that the known human Ser357Gly PC1/3 mutant (PC1/3(S357G)) represents a PC1/3 hypermorph. Conditioned media from human embryonic kidney-293 cells transfected with PC1/3(WT) and PC1/3(S357G) were collected and enzymatic activity characterized. PC1/3(S357G) exhibited a lower calcium dependence; a higher pH optimum (neutral); and a higher resistance to peptide inhibitors than the wild-type enzyme. PC1/3(S357G) exhibited increased cleavage to the C-terminally truncated form, and kinetic parameters of the full-length and truncated mutant enzymes were also altered. Lastly, the S357G mutation broadened the specificity of the enzyme; we detected PC2-like specificity on the substrate proCART, the precursor of the cocaine- and amphetamine regulated transcript neuropeptide known to be associated with obesity. The production of another anorexigenic peptide normally synthesized only by PC2, αMSH, was increased when proopiomelanocortin was coexpressed with PC1/3(S357G). Considering the aberrant enzymatic profile of PC1/3(S357G), we hypothesize that this enzyme possesses unusual processing activity that may significantly change the profile of circulating peptide hormones.